Mencari Keselarasan: Menyingkirkan Dikotomi Work-Life Balance - Darmawijaya, I Gede; Darmaputra, Putu Gede Eka; Sunarsa, I Wayan (Journal of Hospitality Accommodation Management (JHAM), 2024)
This research aims to provide a different perspective on the dichotomy of work and life, which in many work-related studies is considered as suffering that needs to be balanced with non-working life or time. This qualitative research employs content analysis using secondary data sources from journal articles or other publications by experts, researchers, and spiritual practitioners. The findings of this study indicate that researchers use the work-life balance variable as a cause of job satisfaction. In contrast, experts and spiritual practitioners agree that there is only life, and life is where work is life itself. Researchers tend to view happiness as coming from external factors, always associated with compensation, job satisfaction, work environment, and other external stimuli. On the other hand, experts and spiritual practitioners believe, based on their experiences, that happiness is an internal creation, not influenced by external factors because true happiness is an inner experience. Therefore, it is recommended that further research focuses on effective practices of self-understanding leading to the awareness that happiness is not sought but found within.